Disorders of forestomach in cattle and buffaloes of Haryana - KUMAR, ANKIT; POTLIYA, SANDEEP; THAKUR, VIPUL; SINGH, HARPREET; RUHIL, SWATI; BANGAR, YOGESH; BISLA, R S (The Indian Journal of Animal Sciences, 2021)
The study was conducted on 5,689 animals (2,163 cattle; 3,526 buffaloes) during July 2016 to June 2017 to understand the epidemiological features of forestomach disorders in cattle and buffaloes. Diagnosis was made on the basis of history, clinical, haemato-biochemical and radiographic examinations. Overall annual incidence of forestomach disorders was 17.82%, significantly more in buffaloes (19.11%) compared to cattle (15.71%). Impaction was the major forestomach disorder with overall annual incidence of 11.37%, with significantly higher incidence in buffaloes (12.16%) than cattle (10.07%). Different forestomach disorders and their respective incidence were: simple indigestion (SI) (2.6% – 2.45% in cattle and 2.69% in buffaloes), colic (0.49% – 0.64% in cattle and 0.39% in buffaloes), tympany (0.79% – 0.87% in cattle and 0.73% in buffaloes), Lactic acidosis (0.38% – 0.55% in cattle and 0.28% in buffaloes), Traumatic pericarditis (1.12% – 0.69% in cattle, 1.38% in buffaloes), foreign body syndrome (FBS) (0.68% – 0.41% in cattle, 0.85% in buffaloes) and diaphragmatic hernia (DH) (0.59% – 0.0% in cattle and 0.59% in buffaloes). Forestomach disorders mainly occurred during summer and rainy season. Impaction, SI and colic cases were mainly observed in initial lactations whereas cases of tympany were higher in between 4th to 6th lactation. DH and FBS were significantly higher in buffaloes compared to cattle (particularly upto third lactation). The present study indicated that impaction, SI, FBS and DH are most prevalent forestomach disorders in Haryana leading to significant production losses. Hence, research on responsible etiological factors and preventive measures is warranted.